2021
DOI: 10.3390/ph14080708
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Host–Microbiota Interactions in Autophagy and the Pathogenesis of Inflammatory Bowel Disease (IBD)

Abstract: Inflammatory bowel disease (IBD) is a family of conditions characterized by chronic, relapsing inflammation of the gastrointestinal tract. IBD afflicts over 3 million adults in the United States and shows increasing prevalence in the Westernized world. Current IBD treatments center on modulation of the damaging inflammatory response and carry risks such as immunosuppression, while the development of more effective treatments is hampered by our poor understanding of the molecular mechanisms of IBD pathogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 203 publications
(210 reference statements)
0
11
0
1
Order By: Relevance
“…Taken together, IPA produced only by the gut microbiota plays a direct or indirect role in various disease models that have not been previously recognized. Strikingly, IPA is well tolerated in current mouse models with no adverse effects [ 77 , 134 ]. However, there remain many problems and challenges in the clinical application of IPA, which need to be further explored in follow-up research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, IPA produced only by the gut microbiota plays a direct or indirect role in various disease models that have not been previously recognized. Strikingly, IPA is well tolerated in current mouse models with no adverse effects [ 77 , 134 ]. However, there remain many problems and challenges in the clinical application of IPA, which need to be further explored in follow-up research.…”
Section: Discussionmentioning
confidence: 99%
“…It is gratifying that the positive role of IPA in neurological diseases is becoming increasingly recognized by researchers. Indeed, IPA has been used in the clinical development of the neurological disorder, Friedrich’s ataxia [ 77 ]. Thus, IPA has become a research hotspot in the research and clinical usage of the gut–brain axis.…”
Section: The Roles Of Ipa In Host Diseases and Healthmentioning
confidence: 99%
“…Changes in the intestinal barrier can cause bacteria to migrate into the intestinal mucosa or portal vein circulation, which alters the host-microbe interactions that are key to intestinal inflammation[ 36 ]. In particular, gut cells can sense microbe-derived, pathogen-associated molecular patterns through pattern recognition receptors[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in the composition of the gut microbiota can impact the integrity of the gut barrier and are linked with the development of (chronic) inflammatory and metabolic diseases [5][6][7]. Furthermore, the proinflammatory state associated with aging, often referred to as inflammaging, has been associated with changes in the gut microbiome [8][9][10]. Recently, we showed that high abundance of the gut commensals Ruminococcus torques and Escherichia coli, often observed in inflammatory processes such as inflammatory bowel disease [11][12][13], were associated with a pro-inflammatory immune profile in the ageing population with influenza-like illness (ILI) [14].…”
Section: Introductionmentioning
confidence: 99%